MINERALOGY AND MICROSTRUCTURE OF RANTAU DEDAP'S GEOTHERMAL RESERVOIR: HYDROTHERMAL ALTERATION INSIGHTS - Welayaturromadhona Welayaturromadhona; Firman Sauqi Nur Sabila; Mauliate Agustinus Hamonangan Sihotang; Luthfi Rindra Salam; Fifi Izzati (Jurnal Geosaintek, 2025)
The Great Sumatra Fault controls the Rantau Dedap geothermal system in South Sumatra. It is a high-temperature volcano-tectonic system. This study presents a comprehensive mineralogical and microstructural examination of core samples from three deep wells (UJ-A1, UJ-B1, and UJ-C1) at depths ranging from 1,840 to 2,313 m, aiming to elucidate hydrothermal alteration and its impact on reservoir quality. X-ray Diffraction (XRD) and Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDS) analyses demonstrate a distinct propylitic alteration zonation correlated with increasing depth and temperature. UJ-A1 (1840 m) is mainly made up of oligoclase, microcline, and quartz. UJ-B1 (2142 m) is mainly made up of oligoclase-quartz. UJ-C1 (2313 m) is mainly made up of anorthite-quartz with more iron. Anorthite, a calcium-rich plagioclase that stays stable above 280 °C, is found at greater depths. This means that the area is close to a major upflow zone. SEM microstructural analysis reveals hydrothermal breccia textures, characterized by angular fragments within a matrix of secondary minerals, and indicates secondary porosity resulting from mineral alteration. These characteristics suggest that hydraulic brecciation resulting from tectonic activity is essential for the creation and preservation of reservoir permeability. The reservoir's potential is enhanced because it lacks smectite-type clays, which typically block pores. In general, these results indicate that Rantau Dedap is a structurally controlled upflow zone characterized by deep mafic lithologies. The anorthite-quartz assemblage stands out as a key sign for future high-temperature geothermal exploration.